Design of a Digital Temperature and Humidity Measuring Instrument Using ATmega 328P Microcontroller - Apriandi, Hadi; I Made, Satriya Wibawa; I Gde, Antha Kasmawan (BULETIN FISIKA, 2021)
It has been successfully made design of a digital temperature and humidity measuring instrument using ATmega 328P microcontroller. The results of temperature and humidity data are measured using the DHT22 sensor which receives data signals in the form of temperature and humidity. Design of the instrument is placed in the same place as the reference instrument, namely in the instrument shop, then the results of the design of the reference instrument and instrument are processed into graphical form and proven using linear regression equations. The measurement results are displayed on the LCD keypad shield. The results of the instrument design calibration carried out on the reference instrument have a fairly good level of accuracy, namely for air temperature of 99.99% and humidity of 98.34%. From the results of the calibration carried out, it shows that the design of the instrument made has good validity (accuracy and precision).